2014
DOI: 10.1002/chem.201403091
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Grafting of Silatranes to Carbon Interfaces

Abstract: Covalent Si-C grafting of a silatrane cage to a carbon-based interface provides a truly conjugated benzyl-type system in which the 3 c-4 e orbital of the silatrane interacts with the macroscopic π-type substituent (graphite Csp2 network) through hyperconjugation. This process, studied by voltammetry, EIS, FTIR, SEM and DFT modeling, allows one to build carbon-based conducting interfaces with electronically conjugated molecular extensions. Non-conjugated covalent grafting of an alkyl silatrane moiety provides c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…We have recently shown that when a metallatrane carries a relatively hard to ionize 1-substituent, electron withdrawal upon oxidation can directly affect this hyperbond, resulting in persistent cation radicals [10][11][12] with the spin localized inside the atrane cage on a practically planar N atom. 10c,12 Such systems show a great promise for various modern applications, primarily for spin-commutating interfaces 13 and as potential electromechanical actuators. 11,12,14 Driven by the double interest for these compounds and continuing the works on the redox chemistry of intramolecular-coordinated derivatives of the elements of group 14 with pending 15 or included into a rigid structure 10, 11,16 coordinating groups, we envisaged a novel bis-metallatrane system with two fused atrane cages sharing a common nitrogen atom to form a 5c-6e hyperbond capped with two thienyl end-substituents (Scheme 1).…”
mentioning
confidence: 99%
“…We have recently shown that when a metallatrane carries a relatively hard to ionize 1-substituent, electron withdrawal upon oxidation can directly affect this hyperbond, resulting in persistent cation radicals [10][11][12] with the spin localized inside the atrane cage on a practically planar N atom. 10c,12 Such systems show a great promise for various modern applications, primarily for spin-commutating interfaces 13 and as potential electromechanical actuators. 11,12,14 Driven by the double interest for these compounds and continuing the works on the redox chemistry of intramolecular-coordinated derivatives of the elements of group 14 with pending 15 or included into a rigid structure 10, 11,16 coordinating groups, we envisaged a novel bis-metallatrane system with two fused atrane cages sharing a common nitrogen atom to form a 5c-6e hyperbond capped with two thienyl end-substituents (Scheme 1).…”
mentioning
confidence: 99%
“…Electrochemical oxidation of hypervalent metallatranes XM(OCH 2 CH 2 ) 3 N( I,w ith M = Si, Ge, Sn) has been shown to produce radicalc ations (RCs) possessing au nique structure and having ag reat promisef or the potentiala pplications. [1][2][3][4][5][6][7] To cite af ew,t hese might be an ew type of molecular wires, spin switches,a nd electromechanicals ystems. [4c, 5] Their potential in surfacer esearch has been demonstratedf or corrosion protection of metals [7] and functional capping of carbonaceousi nterfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[4c, 5] Their potential in surfacer esearch has been demonstratedf or corrosion protection of metals [7] and functional capping of carbonaceousi nterfaces. [1] This raising interest to the redox chemistry of metallatranes is impeded by as ubstantial gap between the levels of experimental and theoretical works in this field. Remarkably, to date there were even no attempts to calculate the redox potentials of intramolecular complexes of the Group 14 elements, including metallatranes,t hat are anomalously sensitivet ot he media (solvent) effects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations